'Sovereignty of the air': The Indian princely states, the British Empire and carving out of air-space (1911–1933). (2nd January 2022) - Mirza, Priya
ABSTRACT: Who owns the skies? Under British colonialism, the ownership of the skies of India was a contested matter. The onset of aviation presented a challenge to the territorial understanding between the British and semi-sovereign Indian princes, Paramountcy (1858–1947). Technology itself was a tricky area: roadways, railways, telegraphs, and the wireless were nibbling away at the sovereign spheres which Paramountcy had put in place. This paper looks at the history of aviation in princely India, from aviation enthusiasts such as the rulers of Kapurthala, Jodhpur and Bikaner to subversive princes like the Maharaja of Patiala who worked towards a military air force. The paper tracks the three stages of the journey of aviation in princely India, from individual consumption, to the historical context of World War One which aided its access and usage, and finally, the collective princely legal assertion over the vertical air above them in the position, 'sovereignty of air'. The government's civil aviation policy in India remained ambiguous about the princes' rights over the air till 1931 when their sovereignty of the sky was finally recognised. The paper focuses on the Indian princes varied engagement with aviation, modernity and their space in the world.